Effect of rate of arbuscular mycorrhiza inoculum on Tomato (Solanum lycopersicum) seedlings (Bangladesh Journal of Agricultural Research, 2013)
An experiment on the effect of rate of Arbuscular mycorrhiza (AM) inoculum on tomato seedlings was conducted at Bangladesh Agricultural Research Institute, Joydebpur, Gazipur, Bangladesh for two consecutive years. Seven rates of AM inoculum viz., 0, 0.5, 1.0, 1.5, 2.0, 2.5, and 3.0 kg/m2 were tested. Cowdung was used at a rate of 5 kg/m2. Seeds were sown in 10 cm apart lines on 13 November 2007 and 11 November 2008, and the seedlings were thinned out to about 3 cm from seedling to seedling within a week of germination. Roma VF was used as a variety of tomato. Biomass yield, root colonization, spore number, and nutrient uptake by tomato seedlings increased remarkably with the rates of AM inoculum. The biomass yield followed a quadratic trend with the increase of AM inoculum rate from 0 to 2.0 kg/m2 in 2007-08 and 0 to 1.5 kg/m2 in 2008-09. DOI: http://dx.doi.org/10.3329/bjar.v38i3.16974 Bangladesh J. Agril. Res. 38(3): 473-480, September 2013